Marketing Strategy Analysis in Increasing Tourism Ticket Sales Revenue: Study Literature Review - Fitria Ariyani; Rona Tumiur Mauli Carolin Simorangkir; Mochammad Subagio; Nunung Ayu Sofiati; Indra Sani (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this literature research is expected to build hypotheses regarding the influence between variables which can later be used for further research in the scope of marketing management. The literature review research article analyzing marketing strategies in increasing tourism ticket sales revenue is a scientific literature article within the scope of marketing management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this research and is sourced from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Product has an effect on Increasing Tourism Ticket Sales; 2) Price affects the increase in tourism ticket sales; 3) Promotion affects the increase in tourism ticket sales; and 4) Place affects the increase in tourism ticket sales.